2017
DOI: 10.1186/s12955-017-0627-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between misperceptions around weight status and quality of life in adults in Australia

Abstract: BackgroundLimited evidence supports a possible association between a person’s perception of their weight status and their quality of life (QoL). This study evaluates whether misperception around weight status is associated with QoL and the impact of gender on this association.MethodsA cross-sectional survey of Australian adults (n = 1,905 analysed) collected self-reported height and weight (used to estimate BMI), gender and QoL (described using the AQoL-8D). Participants reported whether they perceived their w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
2
6
1
2
Order By: Relevance
“…8,10,11,14,41 Both weight underestimation and overestimation have undesirable consequences on an adult's awareness of the aspects for health-related QoL. 3,5,42 Adults with bodyweight misperception have an impaired QoL, engage in unhealthy lifestyle practices, develop an impaired self-perceived health status, and achieve a body weight such as obesity that contributes to the onset of chronic diseases. 5,20,43 In fact, bodyweight misperception was a significant indicator of obesity for elderly Chinese Americans because they would underestimate their body weight although the BMI indicated that they were "obese."…”
Section: Consequences Of Bodyweight Misperception In Chinese Femalesmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,11,14,41 Both weight underestimation and overestimation have undesirable consequences on an adult's awareness of the aspects for health-related QoL. 3,5,42 Adults with bodyweight misperception have an impaired QoL, engage in unhealthy lifestyle practices, develop an impaired self-perceived health status, and achieve a body weight such as obesity that contributes to the onset of chronic diseases. 5,20,43 In fact, bodyweight misperception was a significant indicator of obesity for elderly Chinese Americans because they would underestimate their body weight although the BMI indicated that they were "obese."…”
Section: Consequences Of Bodyweight Misperception In Chinese Femalesmentioning
confidence: 99%
“…44,45 Bodyweight misperception can impact a person's lifestyle and health-related behavior, which are crucial determinants of health. 5,42 Both underestimation and overestimation of one's body weight pose a high risk for poor physical health and psychosocial dysphoria. 8,14,25,41 For instance, the leading indicator of health status, a measurement of the Health-Related Quality of Life (HRQoL) concept, can be negatively impacted from the effect of bodyweight misperception on overall physical, psychological well-being, life-satisfaction, and quality of living, dimensions of HRQoL.…”
Section: Application Of Findingsmentioning
confidence: 99%
“…ve depressif semptom yaşadıkları belirlenmiştir (12). Fazla kilolu bireylerin vücut ağırlık durumlarını doğru bir şekilde belirleyememesi, etkisiz kilo yönetimi ve yaşam kalitesinin olumsuz etkilenmesi açısından ciddi risk faktörleri olarak vurgulanmaktadır (13)(14)(15). Yapılan araştırmalarda hastalık farkındalığının bozulması ya da fazla kilolu/obez olduğunu kabul etmeme durumunun sağlıklı yaşam tarzı değişikliklerine bir engel olduğu, negatif klinik sonuçlara katkıda bulunduğu ve sağlık kurumuna başvuru oranları ile ilişkili olduğu gösterilmiştir (15)(16)(17).…”
Section: Introductionunclassified
“…The latter may be through dissatisfaction with own weight, which is linked to low self-esteem and further to depression 14. Several studies have found that individuals with overweight/obesity who underestimate their weight report better quality of life than those who have an accurate weight perception,15–18 and recent findings suggest weight underestimation in people with overweight/obesity to be protective against depression 18–20. Interestingly, weight underestimation may also protect against future depression indicating weight perception to matter in a causal relationship with depression development 18.…”
Section: Introductionmentioning
confidence: 99%